LEGAL PROTECTION FOR WORKERS WHO HAVE WORK ACCIDENTS AND NOT REGISTERED IN THE BPJS PROGRAM - Benny Bambang Irawan Nitinegoro; Mahmuda Pancawisma Febriharini (UNTAG Law Review, 2022)
Writing this journal aims to determine legal protection for workers who experience work accidents and are not registered in the BPJS program. In national development the role of manpower is very important, so that protection of manpower is very much needed to guarantee the basic rights of workers/laborers and guarantee equality of opportunity and treatment without discrimination on any basis to realize the welfare of workers/laborers. Guarantee of personal protection and safety and interests during the work relationship.This writing uses a normative juridical approach. The specifications for this writing are "discritical analysis", because it will analyze the main issues under study based on statutory regulations.Workforce protection in the form of compensation in the form of money as a substitute for part of the reduced income as a result of events or circumstances experienced by workers in the form of work accidents, illness, pregnancy, old age and death. If a worker experiences a work accident, he is entitled to receive compensation in the form of money and medical expenses from the BPJS or from the employer if he has not registered as a BPJS participant. for freelance or contract daily workers if there is a work accident which results in him being unable to work, the company provides a policy of bearing hospital costs and not deducting wages on that day and the company is required to register with BPJS for health and employment in accordance with government regulations